Questionnaires based on natural language processing elicit immersive ruminative thinking in ruminators: Evidence from behavioral responses and EEG data - Li, Yulong; Li, Chenxi; Zhang, Tian; Wu, Lin; Lin, Xinxin; Li, Yijun; Wang, Lingling; Yang, Huilin; Lu, Diyan; Miao, Danmin; Fang, Peng (Frontiers in Neuroscience, 2023)
Abstract: Rumination is closely related to mental disorders and can be used as a critical predictor of mental disorders. The presence of masking and fabrication in psychological selection leads to inaccurate detection of psychological disorders. Human natural language is the key to eliciting specific conscious activities, and questionnaires developed by natural language processing (NLP) in psychological tests have the potential to elicit immersive ruminative thinking, leading to changes in neural activities. Electroencephalograph (EEG) is a commonly used technique to detect and record neural activities in human brain. In this study, we used NLP to develop a ruminant questionnaire and recorded the EEG data of ruminators in response to the questionnaire for detecting ruminative thinking. The behavior results revealed that ruminators presented higher arousal rate and longer reaction time in ruminative items of the questionnaire. EEG results showed no significant difference between the ruminators and controls at resting state. However, there existed a significant alternation in the coherence of the entire brain while answering the questionnaire in ruminators. No differences were found in control participants. The behavior and EEG results indicated that the questionnaire could elicit immersive ruminative thinking in ruminators. Additionally, the coherence in EEG could be used as a neuromarker in detecting ruminative thinking, and the questionnaire based on NPL combined with EEG technology was capable to be a potential paradigm for psychological selection.